1968
DOI: 10.1002/app.1968.070120201
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous freezing point depression of swollen gels

Abstract: synopsisThe anomalous freezing point depression, AT, of benzene-swollen vulcanizates has previously been attributed to the limitation of (benzene) crystallite size by the polymer network. This study was initiated to determine the benzene crystallite size in a number of rubber and benzene systems. A special low-temperature specimen holder was designed and constructed in the Cambridge Laboratories for running diffraction patterns at temperatures near -30°C. X-ray line broadening techniques were used to study a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 13 publications
4
24
0
Order By: Relevance
“…It was shown that the smaller the mesh size, the smaller the crystal size and the lower the observed freezing point. This agrees with the results of Boonstra et al, 13 Oikawa and Murakami, 14 and Honiball et al, 16 where a more tightly crosslinked network (i.e., one with a smaller mesh size) produced a larger depression in the freezing point of the solvent. However, these workers determined that the freezing point depression was too large to have been caused solely by a reduction in crystal size.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…It was shown that the smaller the mesh size, the smaller the crystal size and the lower the observed freezing point. This agrees with the results of Boonstra et al, 13 Oikawa and Murakami, 14 and Honiball et al, 16 where a more tightly crosslinked network (i.e., one with a smaller mesh size) produced a larger depression in the freezing point of the solvent. However, these workers determined that the freezing point depression was too large to have been caused solely by a reduction in crystal size.…”
Section: Introductionsupporting
confidence: 92%
“…Many researchers [13][14][15][16][17] have investigated the interaction between a solvent and a rubbery polymer by studying the freezing and melting behavior of the solvent. It has been observed 13,14,16 that the higher the volume fraction of rubber in solvent/rubber mixtures, the lower the freezing point of the solvent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22] Honiball et al 20 suggested that it was the difficulty in nucleation of the solvent which lead to the excess DT f . Using X-ray measurements to study the crystal size of benzene, Boonstra et al 21 concluded that there was no significant difference of crystal size in uncrosslinked and crosslinked rubbers. This work, however, was found to be inconclusive by Jackson and McKenna.…”
Section: Introductionmentioning
confidence: 99%
“…This anomalous freezing-point depression has been widely described by various authors. [13][14][15][16][17] Kuhn and Majer [13] attributed this anomaly to limited crystal growth in the gel, resulting from a mesh formed by chain segments in the polymer network. Hence, a higher vapor pressure can be expected for microcrystals because of their high surface to volume ratio, rendering a decrease in their freezing point.…”
Section: Introductionmentioning
confidence: 99%